2020
DOI: 10.1007/s00417-020-04788-4
|View full text |Cite
|
Sign up to set email alerts
|

Altered microvascular density in patients with systemic lupus erythematosus treated with hydroxychloroquine—an optical coherence tomography angiography study

Abstract: Purpose To evaluate the retinal microvascular density using optical coherence tomography angiography (OCTA) in patients with systemic lupus erythematosus (SLE) treated with hydroxychloroquine (HCQ). Methods Nineteen eyes of 19 patients with SLE (study group) without HCQ retinopathy and 19 eyes of 19 healthy subjects (control group) were included in this study. The study group was divided into patients using HCQ for > 5 years (high-risk group) and < 5 years (low-risk group). The VD data of the 3 × 3 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 24 publications
3
39
1
Order By: Relevance
“…While several SLE studies showed that the FAZ area was enlarged in SLE patients compared to the control group, two studies showed no change in the FAZ area in SLE patients, similar to our study. 16,23,24,25,32 (Table 6) In our study, although SCP VD in the foveal area was found to be lower in SLE patients than that in the HCs, the size and shape of the FAZ in the SCP area were not affected.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…While several SLE studies showed that the FAZ area was enlarged in SLE patients compared to the control group, two studies showed no change in the FAZ area in SLE patients, similar to our study. 16,23,24,25,32 (Table 6) In our study, although SCP VD in the foveal area was found to be lower in SLE patients than that in the HCs, the size and shape of the FAZ in the SCP area were not affected.…”
Section: Discussionmentioning
confidence: 42%
“…Some studies have investigated subclinical retinal involvement and VD in SLE. 10,12,16,20,[22][23][24][25][26] A brief literature review of OCTArelated findings in SLE patients is shown in Table 6. In our study, DCP VD was found to be significantly lower in SLE patients than in HCs in all areas except the perifoveal temporal area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of retinal microvascular changes in CD patients have never been studied. An enlargement of the FAZ has been described in pathologies causing retinal capillary ischemia such as diabetic retinopathy [29] and lupus erythematosus [20]. The microcirculatory damage observed in our population of CD patients may be explained by the inflammation and arthrosclerosis and prothrombotic state that the disease induces.…”
Section: Discussionmentioning
confidence: 56%
“…Altered retinal microcirculation has been described in active IBD [16], and increased arteriolar tortuosity has also been reported in IBD, probably due to systemic vascular damage [17]. In the same way, altered OCT-A findings were described in rheumatoid arthritis, another chronic systemic inflammatory disease with increased cardiovascular risk [18,19], and in lupus erythematosus, which is also associated with a high thrombotic risk [20]. The increased cardiovascular and prothrombotic risk in CD could be associated with a rarefaction of the retinal microcirculation, which can be observed in OCT-A by a decrease of the microvascular density or an enlargement of the central avascular zone [21].…”
Section: Introductionmentioning
confidence: 89%